Karakteristik Pasien Melanoma Maligna di Subbagian Bedah Onkologi RSUP Sanglah Tahun 2015-2016 - Gusti Ngurah Agung Adi Paramartha; I Wayan Niryana; Putu Anda Tusta Adiputra (DiscoverSys Inc., 2019)
Background: Malignant melanoma (MM) is one of the skin malignancies derived from melanocyte cells. It is the most common cause of death, about 75% of all cases of skin cancer. Skin cancer is ranked fourth among the ten most common tumors in Bali.Aim: To know the characteristics of malignant melanoma patients in the sub-section of surgical oncology Sanglah Hospital Year 2015-2016.Method: This study is cross-sectional descriptive research conducted at Sanglah General Hospital in Denpasar. The data obtained in the form of secondary data, patient medical records, as of 2015 till 2016. Data were analyzed using the SPSS program.Result and Conclusion: The results showed that of 11 patients, incidence with the highest proportion of patients with age range 45-59 years number of 4 people (36.3%). The most top gender was women of 6 (54.5%). The highest subtype of Nodular Melanoma (NM) was 7 (63.6%).